2016
DOI: 10.15376/biores.12.1.68-81
|View full text |Cite
|
Sign up to set email alerts
|

Superheated Steam Treatment of Oil Palm Mesocarp Fiber Improved the Properties of Fiber-Polypropylene Biocomposite

Abstract: The effect of fiber surface modification by superheated steam (SHS) treatment and fiber content (30 to 50 wt.%) was evaluated relative to the mechanical, morphology, thermal, and water absorption properties of oil palm mesocarp fiber (OPMF)/polypropylene (PP) biocomposites. SHS treatment of OPMF was conducted between 190 and 230 C for 1 h, then the SHS-treated fiber was subjected to melt-blending with PP for biocomposite production. The biocomposite prepared from SHS-OPMF treated at 210 C with 30 wt.% fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…7b displays fiber splitting and tearing on the surface of B0W1, which meant that stress was transferred from the resin to the fibers ). This revealed a higher interfacial adhesion between the wood and resin (Ahamad Nordin et al 2017). Figure 8 shows the physical-mechanical properties of the boards with different bamboo green mass fractions in fibrous raw materials.…”
Section: Physical-mechanical Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…7b displays fiber splitting and tearing on the surface of B0W1, which meant that stress was transferred from the resin to the fibers ). This revealed a higher interfacial adhesion between the wood and resin (Ahamad Nordin et al 2017). Figure 8 shows the physical-mechanical properties of the boards with different bamboo green mass fractions in fibrous raw materials.…”
Section: Physical-mechanical Analysismentioning
confidence: 96%
“…This was because the surface of the bamboo green was coated with abundant silica and wax (Fig. 1), and these hydrophobic substances made the fibrous raw materials unlikely to agglomerate, which led to a higher fiber dispersion in the boards (Ahamad Nordin et al 2017). Figure 7a shows that there were many small gaps on the surface of B1W0, which reflected a lower interfacial adhesion (Song et al 2017b).…”
Section: Physical-mechanical Analysismentioning
confidence: 99%
“…This can be explained by the improvement in hydrophobicity of the SHStreated OPB fibers as a result of hemicellulose removal, which contributed to improved compatibility and interfacial adhesion between SHS-treated OPB fibers and PP. Apart from that, SHS treatment improved the adhesive characteristics of OPB fibers by removing impurities covering the surface of the fiber, resulted in fibers with relatively clean and rough surface which are favourable for fibers-polymer interaction (Nordin et al, 2017). All of these reasons contributed to the increase in both TS and TM of SHS-treated OPB/ PP biocomposites compared to untreated OPB/PP biocomposites.…”
Section: Mechanical Properties Of Opb Biocompositesmentioning
confidence: 99%
“…This can be explained by better compatibility of SHStreated OPB with PP as compared to untreated OPB, due to the removal of hemicellulose which caused partial removal of hydrophilic component. This ultimately improved interfacial adhesion between SHS-treated OPB fibers and PP matrix which in turn produced biocomposite with better bending and crack propagation resistance (Nordin et al, 2017). On the other hand, segmental movement of the polymer chains can be hindered when natural fibers are introduced into the polymer matrix and this caused the biocomposites to become stiffer and eventually improved the FM as compared to neat PP.…”
Section: Mechanical Properties Of Opb Biocompositesmentioning
confidence: 99%
“…They interpreted that the compatibility of the poplar veneer and HDPE film was improved under thermal treatment; this was achieved by increasing the ability of HDPE molecules to fill the small cavities on the veneer to form mechanical interlock. Ahamad Nordin et al (2017) reported the heat-treated oil palm mesocarp fiber/ polypropylene composites. They pointed out that the heat treatment gave rougher surface topography of the fiber, consequently increasing the effective surface area to which polypropylene could adhere on the fiber surface, thus some treated composites had higher mechanical properties compared with the untreated group.…”
Section: Effects Of the Heat And Alkali Treatments On The Microscopicmentioning
confidence: 99%